Structural cross sections through the Corinth-Patras detachment fault-system in Northern Peloponnesus (Aegean Arc, Greece) - FLOTTÉ, N.; SOREL, D. (Bulletin of the Geological Society of Greece, 2001)
Structural mapping in northern Peloponnesus reveals the emergence of an E-W striking, more than 70km long, low angle detachment fault dipping to the north beneath the Gulf of Corinth. This paper describes four north-south structural cross-sections in northern Peloponnesus. Structural and sedimentological field observations show that in the studied area the normal faults of northern Peloponnesus branch at depth on this major low angle north-dipping brittle detachment. The southern part of the detachment and the related normal faults are now inactive. To the north, the active Helike and Aigion normal faults are connected at depth with the seismically active northern part of the detachment beneath the Gulf of Corinth.